The State of the Death Penalty - Desai, Ankur (2019)
The death penalty is in decline in America and most death penalty states do not regularly impose death sentences. In 2016 and 2017, states reached modern lows in imposed death sentences, with just thirty-one defendants sentenced to death in 2016 and thirty-nine in 2017, as compared with over three hundred per year in the 1990s. In 2016, only thirteen states imposed death sentences, and in 2017, fourteen did so, although thirty-one states retain the death penalty. What explains this remarkable and quite unexpected trend? In this Article, we present new analysis of state-level legislative changes that might have been expected to impact death sentences. First, life without parole (LWOP) statutes, now enacted in nearly every state, might have been expected to reduce death sentences because they give jurors a non-capital option at trial. Second, legislatures have moved, albeit at varying paces, to comply with the Supreme Court’s holding in Ring v. Arizona, which requires that the final decision in capital sentencing be made not by a judge, but by a jury. Third, states at different times have created state-wide public defender offices to represent capital defendants at trial. In addition, the decline in homicides and homicide rates could be expected to contribute to the decline in state-level death sentencing. We find that contrary to the expectations of many observers, changes in the law such as adoption of LWOP and jury sentencing, did not consistently or significantly impact death sentencing. The decline in homicides and homicide rates is correlated with changes in death sentencing at the state level. However, this Article finds that state provision of capital trial representation is far more strongly and robustly correlated with reduced death sentencing than these other factors. The findings bolster the argument that adequacy of counsel has greater implications for the administration of the death penalty than other legal factors. These findings also have implications beyond the death penalty and they underscore the importance of a structural understanding of the Sixth Amendment right to counsel in our system of criminal justice